Respuesta :

So our equation currently is ⇒ [tex]x^2+y^2-10x+8y-8 = 0[/tex]

Let's first move all the constant to one side and group 'like variables' together:

      [tex](x^2-10x)+(y^2+8y) = 8[/tex]

Now lets complete the square of both equations

    [tex](x^2-10x+25)+(y^2+8y +16) = 8 + 25 + 16\\(x-5)^2+(y+4)^2 = 49\\(x-5)^2+(y+4)^2 = 7^2[/tex]

Now we know the circle's general equation format is:

   ⇒[tex](x-h)^2+(y-k)^2 = r^2[/tex]

  • (h, k) ⇒ coordinate of the center of the circle
  • r ⇒ length of radius of circle

Thus the radius of the circle is 7

Hope that helps!